2015
DOI: 10.1111/1440-1630.12250
|View full text |Cite
|
Sign up to set email alerts
|

Occupational performance: a case for self‐determination

Abstract: The term, 'self-determination', implies that individuals have choice and control over aspects of their lives. Individual/family preferences and choices are now core aspects of Australia's National Disability Insurance Scheme, underpinning the importance attributed to these concepts in relation to the fostering of wellbeing. As occupational therapists, in collaboration with our clients, we facilitate and enable occupational performance goals which are personally meaningful and self-endorsed. As such, our profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 40 publications
1
35
0
Order By: Relevance
“…Incorporating a therapy dog into occupational therapy sessions was thought to enhance a sense of emotional security and relatedness for the children involved. Within therapy, a sense of relatedness can provide children with the confidence to take risks and try new things within the learning process (Junkers & Kennedy‐Behr, 2017; Poulsen, Rodger, & Ziviani, 2006; Ziviani, 2015). Although individuals on the autism spectrum are known to experience difficulty developing and maintaining relationships with human social partners, there is increasing evidence to suggest that they are able to develop a secure relationship with animals (Grandin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Incorporating a therapy dog into occupational therapy sessions was thought to enhance a sense of emotional security and relatedness for the children involved. Within therapy, a sense of relatedness can provide children with the confidence to take risks and try new things within the learning process (Junkers & Kennedy‐Behr, 2017; Poulsen, Rodger, & Ziviani, 2006; Ziviani, 2015). Although individuals on the autism spectrum are known to experience difficulty developing and maintaining relationships with human social partners, there is increasing evidence to suggest that they are able to develop a secure relationship with animals (Grandin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…When a child feels competent that they have the skills and external supports required to master a task, they will demonstrate increased willingness to persist (Poulsen et al, 2006; Ziviani, 2015). Parents identified that the incorporation of the therapy dog into the goal‐directed interventions appeared to enhance their child's belief that they could master the skill.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies included those that were autonomy-supportive: providing choice, novelty, fun and variability in the upper limb intervention. The findings of this research adds to the growing evidence that autonomy-supportive strategies help child engagement in therapy in a range of practice contexts (Gilmore et al, 2010;Levac, 2016;Meyns et al, 2018;Miller et al, 2016;Ziviani, 2015).…”
Section: Engaging Children By Providing Autonomy Supportmentioning
confidence: 72%